PERANAN PROSES ASUHAN GIZI TERSTANDAR TERHADAP ASUPAN GIZI, STATUS GIZI DAN LAMA RAWAT PADA PASIEN RAWAT INAP DI RSUP Dr HASAN SADIKIN BANDUNG TAHUN 2010 - , YUfrida Leni Fayakun; , Susetyowati, DCN,M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Malnutrition is prevalent in developed countries, including in Indonesia. This situation can be aggravated in hospital due to inadequate care process. The standardized nutrition care process (SNCP) is a model of nutrition care designed to affect any causes of nutrition problem and give intervention in order to improve nutrient intake, nutrition status and that brings effect to length of stay. Objective: To identify the role of SNCP to nutrient intake, nutrition status and length of stay of inpatients. Method: The study was a quasi experiment that used one group pre test post test design. Samples consisted of fifty one people at risk malnutrition during preliminary study and got SNCP during hospitalization. Data were analyzed related to test. Result: 91,54% of energy intake and 118.07% of protein intake were fulfilled during SNCP with significant increase (p<0.05) as much as 49.08% energy and 62.64% protein. That increased significantly (p<0.05) with weight change & body mass index (BMI) at hospital discharge, as much as 0.96% weight change & 0.99% BMI. The change of nutrition status was not significantly associated with length of stay (p>0.05). Conclusion: During SNCP, nutrition intake and nutrition status of could be increased & was positive correlation, but the change of nutrition status not associated with length of stay.